Fluid Inclusion Study of Epithermal Gold-Base Metal Mineralization System in the Shwebontha Prospect, Monywa Mining District, Central Myanmar Monywa - Toe Naing Oo; Agung Harijoko; Lucas Donny Setijadji (Journal of Applied Geology, 2021)
The Shwebontha Prospect area is one of prominent epithermal Au-Ag prospects in Monywa mining district, central Myanmar, characterized by the appearance of gold-bearing and base metal quartz veins with gold grade is around 3g/t -10.4g/t. The geology of the area consists of the volcanic and volcaniclastic rocks of Upper Oligocene-Middle Miocene Magyigon Formation that served as the host rock of the ore mineralization. This research focused on fluid inclusion study is aimed to know the characteristics of hydrothermal fluids during ore mineralization as well as the possible paleo- depth and temperature of formation of gold-bearing and base metal quartz veins. The mineralization styles are gold-bearing brecciated quartz veins and chalcedonic quartz veins where sulfides are clustered as well as disseminated both in quartz gangue and volcanic host rocks. Those quartz veins include pyrite, sphalerite, galena, chalcopyrite and gold (electrum). Fluid inclusion microthermometry indicates that the ore mineralization is characterized by the values of homogenization temperature range from 158°C to 310°C and salinities range from 0.35 to 2.41wt.% NaCl equiv. This temperature is consistent with the formation temperature of 250°C to 270 °C and also their estimate paleo-depth of formation is between 440m and 640m respectively. Microthermometric data indicates that fluid mixing and dilution were significant processes during ore mineralization and evolution of hydrothermal fluids. Based on the petrography of fluid inclusion, microthermometric measurements and ore minerals assemblage as well as estimation of paleo-depth from the Shwebontha Prospect imply that forming in under shallow level epithermal environment